Production possibility frontiers in phototroph:heterotroph symbioses: trade-offs in allocating fixed carbon pools and the challenges these alternatives present for understanding the acquisition of intracellular habitats - Hill, Malcolm S. (Frontiers in Microbiology, 2014)
Intracellular habitats have been invaded by a remarkable diversity of organisms, and strategies employed to successfully reside in another species’ cellular space are varied. Common selective pressures may be experienced in symbioses involving phototrophic symbionts and heterotrophic hosts. Here I refine and elaborate the Arrested Phagosome Hypothesis that proposes a mechanism that phototrophs use to gain access to their host’s intracellular habitat. I employ the economic concept of production possibility frontiers (PPF) as a useful heuristic to clearly define the trade-offs that an intracellular phototroph is likely to face as it allocates photosynthetically-derived pools of energy. Fixed carbon can fuel basic metabolism/respiration, it can support mitotic division, or it can be translocated to the host. Excess photosynthate can be stored for future use. Thus, gross photosynthetic productivity can be divided among these four general categories, and natural selection will favor phenotypes that best match the demands presented to the symbiont by the host cellular habitat. The PPF highlights trade-offs that exist between investment in growth (i.e., mitosis) or residency (i.e., translocating material to the host). Insights gained from this perspective might help explain phenomena such as coral bleaching because deficits in photosynthetic production are likely to diminish a symbiont’s ability to “afford” the costs of intracellular residency. I highlight deficits in our current understanding of host:symbiont interactions at the molecular, genetic, and cellular level, and I also discuss how semantic differences among scientists working with different symbiont systems may diminish the rate of increase in our understanding of phototrophic-based associations. I argue that adopting interdisciplinary (in this case, inter-symbiont-system) perspectives will lead to advances in our general understanding of the phototrophic symbiont’s intracellular niche.